The Efficacy of Cognitive Behavioral Therapy for Tic Disorder: A Meta-Analysis and a Literature Review - Shou, Songting; Li, Yuanliang; Fan, Guohui; Zhang, Qiang; Yan, Yurou; Lv, Tiying; Wang, Junhong (Frontiers in Psychology, 2022)
Background: At present, tic disorder has attracted the attention of medical researchers in many countries. More clinicians choose non drug therapy, especially cognitive behavioral therapy because of cognitive side effects of drug therapy. But few studies had assessed its efficacy. It is necessary to have a more comprehensive understanding of the literature quality of cognitive behavioral therapy and its intervention effect. Methods: In this study, we searched MEDLINE, EMBASE and Cochrane from the beginning to June 15, 2021 to study the efficacy of cognitive behavioral therapy(CBT) on tic disorder. Only studies using the Yale Global Tic Severity Scae and the control group were included. Results: A total of 12 randomized controlled trials (RCTs) including 536 patients with tic disorders were identified. The results showed that the effect of CBT was better than that of the control group.The pooled SMD was -0.34 (95% CI:-0.61,-0.07). The effect size of CBT differs from different intervention conditions. In seven studies, the subjects' motor tic scores were counted. The sample size of the experimental group was 224 and that of the control group was 218.The pooled SMD was -0.43 (95% CI: - 0.75, - 0.11). Seven studies counted the vocal tic scores of subjects, 224 in the experimental group and 218 in the control group. The pooled SMD was -0.22 (95% CI: -0.54, -0.11). Seven studies counted the tic impairment scores of subjects, 220 in the experimental group and 214 in the control group. The pooled SMD was -0.48 (95% CI: -0.73, -0.23). Conclusions: The literature shows that different CBT can significantly reduce the total score of tic disorder and the score of motor tic, but cannot significantly reduce the score of vocal tic. In the future, we need more new interventions to improve the symptoms of different patients, especially vocal tic.